Underwater colonoscopy with endoscopic mucosal resection in cecum - Steshenko, A.; Didenko, E. (My University, 2024)
Aims Underwater endoscopic mucosal resection (UEMR) is a technique for the removal of colorectal nonpedunculated lesions. The our study aim is to compare the efficacy and safety of UEMR versus conventional endoscopic mucosal resection in patients with cecal lesions.
Keywords: тези доповідей